Hemoperitoneum due to complicated jejunal diverticulum - Maglione, Hugo; Gateño, Nisso (Cirugía del Uruguay, 1979)
Pathogenesis of hemoperitoneum, secondary to diverticulum of jejunum is discussed in connection with the case of a patient suffering from this condition as a consequence of a single diverticulus.